Retrospective evaluation of patients with vitamin B12 deficiency in the pediatrics outpatient clinic: Vitamin B12 deficiency in the pediatrics - Yavuz, Sinan; Kaya , Huseyin; Sert , Abdullah; Yigit , Ozgül (Journal of Surgery and Medicine, 2024)
Background/Aim: This study examines patients diagnosed with vitamin B12 deficiency in our department. Although rare, vitamin B12 deficiency is one of the causes of megaloblastic anemia, which can lead to negative outcomes in patients. We aim to promote earlier diagnosis to protect patients from these negative effects. Therefore, this study will contribute to raising awareness in the literature. Methods: Retrospectively, we included a total of 127 outpatient children, aged 0–18 years (0–215 months), who were diagnosed and treated for vitamin B12 deficiency at the Bagcilar Training and Research Hospital Child Health and Disease Clinic between October 2014 and February 2015. Results: Among the patients, 67 (53%) with vitamin B12 deficiency were female, while 60 (47%) were male, indicating a higher occurrence in girls. Vitamin B12 deficiency was most commonly observed in the age groups of 0-2 years and 12-17 years (adolescents). The mean vitamin B12 level was 168.1 (34.1) pg/mL, the mean hemoglobin level was 12 (1.9) g/dL, and the mean MCV (mean corpuscular volume) was 78.4 (8.1) fl. Anemia was observed in 38% of the patients, bicytopenia in 4%, neutropenia in 6%, thrombocytopenia in 9%, pancytopenia in 3%, and macrocytosis in 2%. Non-iron-deficient patients showed no difference in mean hemoglobin and RDW (red cell distribution width) when compared to iron-deficient patients. However, their B12 levels were lower. The prevalence of iron deficiency did not differ between girls and boys. Comparing patients with vitamin B12 levels lower than 150 pg/mL to those with higher levels, there were no significant differences in average Hb, MCV, and RDW. Conclusion: It should be noted that macrocytic anemia is not exclusive to vitamin B12 deficiency. Vitamin B12 deficiency can manifest as normocytic anemia and should not be overlooked in biochemical assessments. It is recommended to conduct nationwide and regional prevalence studies to evaluate vitamin B12 deficiency as a public health issue and to develop new solutions accordingly.